활막 세포에서 HCV Core 단백에 의한 Interleukin-8 발현 유도 - 왕진상(Wang, Jin-Sang); 허원희(Her, Won-Hee); 김소연(Kim, So-Yeon); 윤승규(Yoon, Seung-Kew) (Immune network, 2006)
Background: Rheumatoid arthritis (RA) is a chronic and systemic inflammatory disease that is characterized by invasive synovial hyperplasia, leading to progressive joint destruction. Recent studies have described that RA is caused by virus, bacteria or outside material. Approximately 2 to 20% of RA cases arc reported to be associated with infected hepatitis C virus (HCV). However, the mechanisms underlying virus-induced RA are still unknown. Moreover, few molecular studies have addressed the inflammatory aspects of HCV-associated autoimmune RA. In this study, we aimed to determine whe ther or not another HCV core protein transactivates the IL-8 gene expression, prototypic chemokine, in synovial cell. Methods: To establish the HCV core expressing stable synovial cell line, pCI-neo-core, a plasmid encoding HCV core protein, were transfected to HIG-82 cell line that is an established cell line from rabbit periaricular soft tissue. We examined the morphological changes and cell cycle distribution of HIG-82 cells with expression of HCV core protein by inverted microscopy and flow cytometry analysis, respectively. Also, we determined the mRNA levels of Interleukin (IL)-6 and IL-8 related to the inflammation by RT-PCR and then analyzed regulation of IL-8 expression by the NF-${κ}B$ pathway. Results: Our study showed no significant differences in morphology and cell cycle between HIG-82 control cell line and HIG-82 expressing HCV core protein. However, expression of HCV core protein induces the IL-8 mRNA expression in HIG-82 core cells via activated NF-${κ}B$ pathway. Conclusion: These results suggest that HCV core protein can lead to enhanced IL-8 expression. Such a proinflammatory role may contribute to the etiologic pathogenesis in RA patients with HCV infection.